LOCAL ANESTHETIC MYOTOXICITY - B. K. Romanov; A. P. Pereverzev; A. N. Mironov; N. D. Bunyatyan; V. K. Lepakhin (Безопасность и риск фармакотерапии)
The article presents the mechanisms of development and methods of correction of myotoxicity associated with use of local anesthetics